2021
DOI: 10.1080/24740527.2021.1999796
|View full text |Cite
|
Sign up to set email alerts
|

Developmental mechanisms of CPSP: Clinical observations and translational laboratory evaluations

Abstract: Understanding mechanisms that underly the transition from acute to chronic pain and identifying potential targets for preventing or minimizing this progression have specific relevance for chronic postsurgical pain (CPSP). Though it is clear that multiple psychosocial, family, and environmental factors may influence CPSP, this review will focus on parallels between clinical observations and translational laboratory studies investigating the acute and long-term effects of surgical injury on nociceptive pathways.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 144 publications
0
8
0
Order By: Relevance
“…Some scholars have reported that the probability of CPSP at 3 and 6 months after traditional open thoracic surgery is about 57% and 47%, respectively, and although minimally invasive surgery can reduce the surgical incision and relieve postoperative acute pain, CPSP is still one of the most signi cant complications [23,24]. The onset of CPSP may be related to a series of anatomical, physiological, and biochemical changes but the exact mechanism is still unclear [25]. The de nition of CPSP is based on the healing time of normal tissues (3 months), but this time frame is somewhat random, likely because the time of tissue healing varies greatly among different individuals and is affected by various systemic and local factors, surgical procedures, and anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have reported that the probability of CPSP at 3 and 6 months after traditional open thoracic surgery is about 57% and 47%, respectively, and although minimally invasive surgery can reduce the surgical incision and relieve postoperative acute pain, CPSP is still one of the most signi cant complications [23,24]. The onset of CPSP may be related to a series of anatomical, physiological, and biochemical changes but the exact mechanism is still unclear [25]. The de nition of CPSP is based on the healing time of normal tissues (3 months), but this time frame is somewhat random, likely because the time of tissue healing varies greatly among different individuals and is affected by various systemic and local factors, surgical procedures, and anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the proposed mechanisms that underly the transition from acute to chronic pain states is necessary to identify potential targets to prevent or minimize persistent pain. 30,31 There are a number of relevant publications that • Anxiety sensitivity 9,[18][19][20][21][22] • Perception of pain unpleasantness 17,19,21 • Fear of pain 23 • Fear of re-injury 23 • Poor coping strategies 24 • Depressive symptoms 15,25 • Tendency to catastrophize 3,16,[18][19][20]24,26 • Sleep quality 15,23…”
Section: Mechanismsmentioning
confidence: 99%
“…• Surgery Type a. General Orthopedic 3,11,15,28 (2-54% prevalence) b. Spinal Fusion 9,18 (11-54% prevalence) c. Thoracotomy 29,30 (2-28% prevalence) d. Inguinal Hernia 28,31 (2-9% prevalence) e. Urologic 28…”
Section: Intraoperativementioning
confidence: 99%
See 1 more Smart Citation
“…For an overview over the latest studies describing associations of factors and development of CPSP, refer to Tables 1 and 2. Additionally to these recently published studies, the bio-molecular mechanisms of the transition from acute to CPSP are described in three comprehensive reviews 6,95,96▪▪ . This review focuses on adults; for comprehensive reviews on children and adolescents, see refs 96▪▪–99▪ .…”
Section: Introductionmentioning
confidence: 99%